The Sustainability of Indonesia Pakistan Palm Oil Supply Chain - Diana Chalil; Riantri Barus (Jurnal Manajemen & Agribisnis, 2018)
With high consumption and low production rates, Pakistan appears as one of the main palm oil importers in the world. Among all vegetable oils, palm oil price appears to be the lowest, thus dominating the vegetable oil import market. Indonesia and Malaysia are the two main exporters, in which Pakistan alternately imports palm oil. Within such conditions, this study aims to analyze the sustainability of Indonesia Pakistan supply chain by estimating (i) the influencing factors of Pakistan palm oil import volume from Indonesia, (ii) the price co-integration in the Indonesian-Pakistan palm oil supply chain, and (iii) the adjustments of the short run dynamics towards the long run equilibrium. Using monthly data from 2010 to 2016, the sustainability was analyzed with Auto Regressive Distributed Lag model and Vector Error Correction Model. The results show Pakistan palm oil import volume is significantly influenced by the price of Pakistan’s palm oil import, trade balance and soybean oil price. The lower the palm oil import price, the higher the volume palm oil imported to Pakistan. The import price is co-integrated with all prices along the Indonesia Pakistan supply chain but no error correction towards long run equilibrium, which is partly reflecting impact of Pakistan Government interventions in palm oil trade. Based on these results, it can be concluded that price is the most influencing factor of the Pakistan palm oil import, thus Indonesia Pakistan supply chain could be sustained if the Indonesian palm oil selling price remains competitive. Therefore, Indonesian producers need to increase their productivity and reduce their production costs in all stages of the supply chain, including those among the oil palm smallholders.Keywords: palm oil, supply chain, autoregressive distributed lag, error correction